Has time come for the genetic management of sea bass? - Volckaert, F. (1997)
Since 1980 the industrial production of European sea bass has risen considerably up to at least 18,000 MT in 1996 ( see also Josupeit, Aquaculture Europe 20(2):-12, 1995). This growth is remarkable since few were able to culture the species in the seventies. Several "classical" stages of development can be observed; they are typical of a rapidly expanding bioindustry.